Three-Dimensional Printed Model and Virtual Reconstruction: An Extra Tool for Pediatric Solid Tumors Surgery - Ángela Sánchez-Sánchez; Óscar Girón-Vallejo; Ramón Ruiz-Pruneda; Maria Fernandez-Ibieta; Darío García-Calderon; Vanesa Villamil; María Cristina Giménez-Aleixandre; Carlos Andrés Montoya-Rangel; Juan Pedro Hernández Bermejo (European Journal of Pediatric Surgery Reports, 2018)
Abstract